Performance Analysis of Savonius Rotor Based Hydropower Generation Scheme with Electronic Load Controller - Pudur, Rajen; Gao, Sarsing (Journal of Renewable Energy, 2016)
This paper describes the performance of electronic load controller (ELC) of asynchronous generator (AG) coupled to an uncontrolled Savonius turbine and variable water velocity. An AC-DC-AC converter with a dc link capacitor is employed to maintain the required frequency. The ELC which is feeding a resistive dump load is connected in parallel with the generating system and the power consumption is varied through the duty cycle of the chopper. Gate triggering of ELC is accomplished through sinusoidal pulse width modulation (SPWM) by sensing the load current. A MATLAB/Simulink model of Savonius rotor, asynchronous generator, ELC, and three-phase load is presented. The proposed scheme is tested under various load conditions under varying water velocities and the performances are observed to be satisfactory.